Systemic Lupus Erythematosus: Immunologic Profile Associated to Clinical Manifestations in 30 Patients in the University Hospital of Cotonou, Benin - ADEGBIDI, HUGUES DANIEL GBADEBO (My University, 2017)
Objective: The aims to describe the profile of antinuclear autoantibodies and their association with the clinical manifestations of Systemic Lupus Erythematosus (SLE). Methods: A 15-year and 7-month retrospective, analytical, and multicenter study included patients fulfilling at least four of American College of Rheumatology criteria of SLE seen in Dermatology, Internal Medicine and Rheumatology Departments of two different hospitals in Cotonou. Results: Thirty patients were recorded. The sex ratio M: F was 0.15 and the mean age was 33.1 years +/- 14.2 years. Cutaneous (26/30) and musculoskeletal (23/30) lesions were predominant. Antinuclear antibodies were present in all patients. They were specific for antiDNA (22/30) anti-nucleosome (19/30), anti-Sm (18/30), anti-RNP (17/30) and anti-SSA (16/30). Anti-DNA antibodies were associated with musculoskeletal manifestations (p = 0.02); Anti-nucleosomes with malar rash (p = 0.01) and discoid lupus lesions (p = 0.02); Anti-Sm and anti-RNP to kidney disorders (p ≤ 0.02), anti-SSA to malar rash (p = 0.05) and haematologic signs (p = 0.03). Conclusion: Some immuno-clinical correlations of SLE on dark skin have been confirmed and others have been highlighted. This reflects the intricacy of environmental and genetic factors that underlie interracial and intra-racial differences.
Keywords: Connective tissue disease; Systemic lupus erythematosus; Antinuclear antibodies; Immuno-clinical association; Benin